Harpers Illustrated Biochemistry / Victor W. Rodwell ... [et al.]. - Rodwell, Victor W. (New York : McGraw-Hill Education, 2018)
Annotation Gain a thorough understanding of the principles ofbiochemistry as they relate to the study of clinical medicineTHE BEST REVIEW FOR THE USMLE!The Thirtieth Edition of Harper's Illustrated Biochemistry combines outstanding full-colorillustrations with authoritative integrated coverage of biochemical disease and clinical information. Using brevity and numerous medically relevant examples, Harper's presents a clear, succinct review of the fundamentals of biochemistry that every student must understand in order to succeed in medical school.All fifty-eight chapters emphasize the medical relevance of biochemistryFull-color presentation includes more than 600 illustrationsEach chapter includes a section on BiomedicalImportance and a summary of the topics coveredReview questions follow each of the eleven sectionsCase studies in every chapter emphasize the clinical relevance to biochemistryNEW coverage of toxic naturally-occurring amino acids; extraterrestrial biomolecules; computer-aided drug design; the role of complement cascade in bacterial and viral infection; secreted mediators of cell-cell signaling between leukocytes; the role of mast cells, basophils, andeosinophils; and the hazard of antioxidants that down-regulate radical signaling for apoptosis and increase risk of cancerApplauded by medical students for its current and engaging style, Harper's Illustrated Biochemistry is an essential for USMLE review and the single best reference for learning the clinical relevance of any biochemistry topic.
Includes bibliographical references and index.
Scholarly & Professional
Keywords: Harper; Biochemistry